2023
DOI: 10.1007/s10639-023-11681-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of teacher-student interaction on students’ classroom well-being under online education environment

Abstract: The students’ classroom well-being of college students has been widely concerned in online education researches. In order to implement effectively online education in colleges and universities, based on person-context interaction theory, this study investigates a theoretical model of the impact of teacher-student interaction, sound richness, sound pleasure, perceived ease of use and perceived usefulness on students’ classroom well-being. By surveying 349 college students receiving online education, the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 79 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…El Hedhli et al (2013) found that shopping mall convenience significantly and positively predicts shopping well-being. Xiao et al (2023) found direct relationship between ease of use and well-being. The hypothesis below was thus formulated: H4.…”
Section: Perceived Convenience On Subjective Well-beingmentioning
confidence: 84%
“…El Hedhli et al (2013) found that shopping mall convenience significantly and positively predicts shopping well-being. Xiao et al (2023) found direct relationship between ease of use and well-being. The hypothesis below was thus formulated: H4.…”
Section: Perceived Convenience On Subjective Well-beingmentioning
confidence: 84%
“…Studies have found that learner intentions can affect behavior intentions to various degrees, with a deeper degree of influence and a wider range of influences. Learner intentions can be improved by increasing the perceived usefulness and perceived ease of use of the technology (Alsakka & Orabi, 2023;Xiao et al, 2023).…”
Section: Results Analysismentioning
confidence: 99%
“…TS may be provided to students by EFL teachers in a variety of ways, including by presenting additional resources and materials that provide excellent instances and clear explanations, as well as by making helpful recommendations for improving their English. This form of assistance is regarded as an effective scaffolding mechanism, enabling instructors to provide guidance to learners in order to enhance their language learning process by using more effective tactics [ 40 , 41 ]. As a result, experiencing a sense of achievement enhances their pleasure in academics and boosts their self-assurance.…”
Section: Discussionmentioning
confidence: 99%